A review on the exploitation of biodegradable magnesium-based composites for medical applications. (9th January 2018) - Yang, Jingxin; Koons, Gerry L; Cheng, Guang; Zhao, Linhui; Mikos, Antonios G; Cui, Fuzhai
Abstract: In recent years, materials science research based on magnesium (Mg) alloys has increased significantly due to their notable advantages over traditional metals. However, magnesium alloys are susceptible to excessive degradation and subsequent disruption of mechanical integrity; this phenomenon limits the utility of these materials. Mg alloys can thus be combined with other materials to form composites for medical applications. The present article describes key advances in and considerations for the development of biodegradable Mg-based composites (BMCs). The primary characteristics of these materials include their controllable degradation rates, tunable mechanical properties, adjustable structures to promote tissue repair, improved biocompatibility, and added functionality according to the purpose of the applications. Here we provide an overview of the current research on and development status of BMCs for biomedical materials, including the present limitations and challenges of their use. Finally, this paper comprehensively discusses the most promising directions of future development for these materials.